Features of Odontogenic Sinusitis Associated With Dental Implants. (18th February 2022) - Park, Marn Joon; Park, Han Ick; Ahn, Kang‐Min; Kim, Ji Heui; Chung, Yoo‐Sam; Jang, Yong Ju; Yu, Myeong Sang
Abstract : Objectives: With the increase in dental implants for tooth loss, odontogenic sinusitis following maxillary dental implants is frequently encountered in otorhinolaryngology practice. The authors aimed to reveal the association between implant extrusion into maxillary sinus, along with implant‐related complications in patients diagnosed with implant‐related odontogenic sinusitis (IR‐ODS). Study Design: Case–control study. Methods: This study enrolled 60 patients who received functional endoscopic sinus surgery due to IR‐ODS. The preoperative sinus computed tomography was retrospectively reviewed. Among the 120 maxillary sinuses of the 60 patients, 68 sides were diagnosed with IR‐ODS sides, whereas 27 sides showed no clinical or radiological evidence of this condition after the implant insertion and were defined as the control sides. Statistical analysis between these two groups was conducted, in addition to odds ratio (OR) calculations for associations with IR‐ODS. Results: The mean age of the IR‐ODS subjects was 59.5 ± 19.1, with a male to female ratio of 32/28 (53.3%/46.7%). Implants extruding by more than 4 mm into the maxillary sinus, peri‐implantitis, bone graft disruption–extrusion were associated with a significantly higher incidence in the IR‐ODS ( p  = 0.035, p  = 0.003, p  = 0.011, respectively). The IR‐ODS sides showed an adjusted‐OR (95% confidence interval) of 27.4 (2.7–276.5) for extrusion length >4 mm, 11.8 (3.0–46.5) for peri‐implantitis, and 34.1 (3.3–347.8) for bone graft disruption ( p  = 0.005, p  < 0.001, and p  = 0.003, respectively). Conclusion: Maxillary dental implants extruding more than 4 mm into the maxillary sinus, peri‐implantitis, and disrupted–extruded bone grafts show significant association with IR‐ODS. Level of Evidence: 4 Laryngoscope, 133:237–243, 2023